Development and implementation of a Dependable, Simple, and Cost-effective (DSC), open-source running wheel in High Drinking in the Dark and Heterogeneous Stock/Northport mice - Grigsby, Kolter; Usmani, Zaynah; Anderson, Justin; Ozburn, Angela (Frontiers in Behavioral Neuroscience, 2024)
Maintaining healthy and consistent levels of physical activity (PA) is a clinically proven and low-cost means of reducing the onset of several chronic diseases and may provide an excellent strategy for managing mental health and related outcomes. Wheel-running (WR) is a well-characterized rodent model of voluntary PA; however, its use in biomedical research is limited by economical and methodical constraints. Here, we showcase the DSC (Dependable, Simple, Cost-effective), opensource running wheel by characterizing 24-hr running patterns in two genetically unique mouse lines: inbred High Drinking in the Dark line 1 [iHDID-1; selectively bred to drink alcohol to intoxication (and then inbred to maintain phenotype)] and Heterogeneous Stock/Northport (HS/Npt; the genetically heterogeneous founders of iHDID mice). Running distance (km/day), duration (active minutes/day) and speed (km/hour) at 13-days (acute WR; Experiment 1) and 28-days (chronic WR; Experiment 2) were comparable to other mouse strains, suggesting the DSC-wheel reliably captures murine WR behavior. Analysis of 24-hour running distance supports previous findings, wherein iHDID-1 mice tend to run less than HS/Npt mice in the early hours of the dark phase and more than HS/Npt in the late hours of dark phase/early light phase. Moreover, circadian actograms were generated to highlight the broad application of our wheel design across disciplines. Overall, the present findings demonstrate the ability of the DSC-wheel to function as a high-throughput and precise tool to comprehensively measure WR behaviors in mice.